Analisis Mengelola Perubahan dalam Suatu Organisasi Daerah - Padlan Syafrin Azwir; Siti Aisyah (Universitas Muhammadiyah Enrekang, 2022)
This study discusses the management of change in the organization. To manage change, there are several stages that leaders need to go through, including recognizing signs of the need for change in the organization, recognizing the type of change, steps for change and managing resistance to change. Without understanding these stages, change management will not be able to achieve the expected results or even create various resistances to change. To be effective, change management needs to be supported by the leader's commitment to change and the presence of change agents who are able to play their role. When the leader is less sensitive to change or the leadership function is less than optimal, the most likely to apply is a change at the behavioral and social levels because changes at the technical-structural level require the leader's power to carry it out.